Children Learning About Secondhand Smoke (CLASS II): protocol of a pilot cluster randomised controlled trial. Issue 8 (25th August 2015) - Siddiqi, Kamran; Huque, Rumana; Jackson, Cath; Parrott, Steve; Dogar, Omara; Shah, Sarwat; Thomson, Heather; Sheikh, Aziz
Abstract : Introduction: Exposure to secondhand smoke (SHS) increases children's risk of acquiring chest and ear infections, tuberculosis, meningitis and asthma. Smoking bans in public places (where implemented) have significantly reduced adults' exposure to SHS. However, for children, homes remain the most likely place for them to be exposed to SHS. Additional measures are therefore required to protect children from SHS. In a feasibility study in Dhaka, Bangladesh, we have shown that a school-based smoke-free intervention (SFI) was successful in encouraging children to negotiate and implement smoking restrictions in homes. We will now conduct a pilot trial to inform plans to undertake a cluster randomised controlled trial (RCT) investigating the effectiveness and cost-effectiveness of SFI in reducing children's exposure to SHS. Methods and analysis: We plan to recruit 12 primary schools in Dhaka, Bangladesh. From these schools, we will recruit approximately 360 schoolchildren in year 5 (10–12 years old), that is, 30 per school. SFI consists of six interactive educational activities aimed at increasing pupils' knowledge about SHS and related harms, motivating them to act, providing skills to negotiate with adults to persuade them not to smoke inside homes and helping families to 'sign-up' to a voluntary contract to make their homes smoke-free. Children in the control arm will receive the usual education. We will estimate: recruitment and attrition rates, acceptability, fidelity to SFI, effect size, intracluster correlation coefficient, cost of intervention and adverse events. Our primary outcome will consist of SHS exposure in children measured by salivary cotinine. Secondary outcomes will include respiratory symptoms, lung function tests, healthcare contacts, school attendance, smoking uptake, quality of life and academic performance. Ethics and dissemination: The trial has received ethics approval from the Research Governance Committee at the University of York. Findings will help us plan for the definitive trial. Trial registration number: ISRCTN68690577.